(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Bochdalek hernia (BH) is the most common type of congenital diaphragmatic hernia and constitutes 85% of cases. In adults BH is extremely rare. Most of them are asymptomatic. We present a case of BH in an adult patient to point out the importance of clinical examination and computed tomography (CT) scan in reaching the exact diagnosis. A 17-year-old male was presented to the surgery department with a 3-days history of recurrent abdominal pain, vomiting and unable to lie flat. The BH was confirmed on computed tomography (CT) imaging and the patient underwent emergency laparotomy and per-operatively we found part of stomach, greater omentum, splenic flexure of colon along with spleen herniated into the left hemithorax through a defect of approximately 8x6cm in the left postero-lateral aspect of the diaphragm. Reduction of hernia contents and surgical repair of the defect was done with non-absorbable suture. His post-operative period was uneventful. Although rare, this disorder should be recognized and treated appropriately to avoid complications. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 64-67